Occurrence, geochemical fractionation, and environmental risk assessment of major and trace elements in sewage sludge. (1st November 2019) - Nkinahamira, François; Suanon, Fidèle; Chi, Qiaoqiao; Li, Yeyun; Feng, Meiling; Huang, Xiaoying; Yu, Chang-Ping; Sun, Qian
Abstract: Industrialization and accelerated population growth have created a huge amount of sewage sludge. Many studies have reported the sewage sludge as a sink of major and trace elements, but less is known about their geochemical fractionations. In order to assess the mobility, the distribution, bioavailability, and toxicity of those elements in sludge, we collected the sewage sludge samples from all the seven wastewater treatment plants in Xiamen City, China. Results revealed a strong spatial variation and the occurrence of 48 elements with concentrations ranging from 1.00 × 10 - 2 mg kg −1 (Re) to 9.03 × 10 1 g kg −1 (Fe) on the basis of dry sludge weight. Sequential extraction procedure showed that residual and oxidizable fractions were the main geochemical fractions of most studied elements. However, Ca, Mn, Sr, and Ni were mainly bound to acid-exchangeable fractions, while Fe, Zn, Cd, Cr, Co, and V were mainly distributed in the reducible fractions. The contamination factor and risk assessment code indicated that Ni, Cu, Zn, Cd, Cr, Co, Sr, Ca, Mn, Mo, Re, and W were highly mobile with less retention time and exerted high environmental risks through sludge land application. The sludge disposal strategy should consider not only the total concentrations of a broad range of elements but also their bioavailability. Graphical abstract: Image 1 Highlights: 48 elements were detected in sewage sludge from city-wide sampling. Network analysis revealed the co-occurrence among specific elements. Residual and oxidizable fractions turned out to be the major geochemical fractions. Ni, Cu, Zn, Cd, Cr, Co, Sr, Ca, Mn, Mo, Re, and W exerted high ecological risks.